Connexin43 Hemichannel Targeting With TAT-Gap19 Alleviates Radiation-Induced Endothelial Cell Damage - Ramadan, Raghda; Vromans, Els; Anang, Dornatien Chuo; Goetschalckx, Ines; Hoorelbeke, Delphine; Decrock, Elke; Baatout, Sarah; Leybaert, Luc; Aerts, An (Frontiers in Pharmacology, 2020)
Background: Emerging evidence indicates an excess risk of late occurring cardiovascular diseases, especially atherosclerosis, after thoracic cancer radiotherapy. Ionizing radiation (IR) induces cellular effects which may induce endothelial cell dysfunction, an early marker for atherosclerosis. In addition, intercellular communication through channels composed of transmembrane connexin proteins (Cxs), i.e. Gap junctions (direct cell-cell coupling) and hemichannels (paracrine release/uptake pathway) can modulate radiation-induced responses and therefore the atherosclerotic process. However, the role of endothelial hemichannel in IR-induced atherosclerosis has never been described before. Material and Methods: Telomerase-immortalized human Coronary Artery/Microvascular Endothelial cells (TICAE/TIME) were exposed to X-rays (0.1 and 5 Gy). Production of reactive oxygen species (ROS), DNA damage, cell death, inflammatory responses, and senescence were assessed with or without applying a Cx43 hemichannel blocker (TAT-Gap19). Results: We report here that IR induces an increase in oxidative stress, cell death, inflammatory responses (IL-8, IL-1β, VCAM-1, MCP-1, and Endothelin-1) and premature cellular senescence in TICAE and TIME cells. These effects are significantly reduced in the presence of the Cx43 hemichannel-targeting peptide TAT-Gap19. Conclusion: Our findings suggest that endothelial Cx43 hemichannels contribute to various IR-induced processes, such as ROS, cell death, inflammation, and senescence, resulting in an increase in endothelial cell damage, which could be protected by blocking these hemichannels. Thus, targeting Cx43 hemichannels may potentially exert radioprotective effects.